The Impact of Population Migration on the Spread of COVID-19: A Case Study of Guangdong Province and Hunan Province in China - Xing, Guo-Rong; Li, Ming-Tao; Li, Li; Sun, Gui-Quan (Frontiers in Physics, 2020)
On the eve of the Spring Festival in 2020, the coronavirus disease 2019 (COVID-19) was reported. Subsequently, Chinese governments at all levels took emergency measures to control the spread of COVID-19 among people. Guangdong and Hunan are large population floating provinces. The spread of COVID-19 is affected by population migration. Before the Spring Festival, Guangdong and Hunan Provinces dominated population export and import respectively; after the Spring Festival, the trend of population flow was reversed by resumption of work. Taking Guangdong and Hunan as examples, we establish a three-stage dynamical modeling to study the impact of population migration on the spread of COVID-19. The result reveals that Guangdong Province mainly emigrated the population and the scale of infection was reduced before the Spring Festival. However, the situation in Hunan Province was just the opposite. After the Spring Festival, work resumption was taking place across China and the migration of Guangdong may cause a second outbreak of the epidemic. While people in Hunan leave the province to work, the migration of population will have little effect on the spread of COVID-19.